Uthman ibn Affan : the third of the four rightly-guided caliphs - "Aziz, Maulvi Abdul" (Darussalam, Riyadh, 2012)
This volume is the third in the series, focusing on Uthman ibn Affan (R.A), the third of the Four Rightly Guided Caliphs. The book is divided into seven chapters, each highlighting significant aspects of Uthman's life and leadership